Unraveling the Myths of Rural vs. Urban Academic Achievement Drivers - Beatriz-Afonso, Ana; Cruz-Jesus, Frederico (Ital Publication, 2024)
The generalized migration of individuals from rural to urban areas is a global phenomenon that entails many divides, education being one of them. However, there is a lack of understanding regarding whether the factors driving higher academic achievement (AA) differ between urban and rural students. This study uses data from almost every student in Portugal who took the Portuguese and/or mathematics high school national exams. By applying OLS, the aim is to identify the AA drivers and compare these drivers between urban and rural areas. Among the key findings, variables related to academic background emerged as the strongest predictors of AA, regardless of the environment. Additionally, ICT access is insignificant in urban and rural areas, while socio-economic status does not significantly impact AA amongst rural students. These findings highlight the need for tailored interventions that address the unique challenges faced by students in different areas, with a particular focus on enhancing academic support structures to improve educational outcomes. To the best of our knowledge, this study is the first to utilize data encompassing virtually every student in an entire country to compare and understand the differences in the determinants of AA between urban and rural areas. Doi: 10.28991/ESJ-2024-08-06-010 Full Text: PDF